Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan di PT Indah Logistik Cargo Cabang Medan - Nadya Dwita Muzri; Dewi Comala Sari; Annalisa Sonaria Hasibuan; Djames Siahaan; Harris Pinagaran Nasution (Universitas 45 Surabaya, 2024)
This research aims to examine the influence of the work environment and work motivation on employee performance at PT Indah Cargo Medan. A conducive work environment and high work motivation are believed to have an important role in increasing employee productivity and work quality. The research method used was quantitative and regression analysis, with the type of data collection used being primary where the sample was taken as many as 84 respondents by circulating a questionnaire via Google Form using the Saturated Sampling technique. The results of this research show that the variables work environment, work motivation simultaneously have a significant effect on employee performance as evidenced by Fcount>Ftable, namely 23.591>3.11. The work environment has a significant effect on employee performance. This result is proven by Tcount>Ttable 2.876>1.989. Work motivation has a significant effect on employee performance. This result is proven by Tcount>Ttable 2.876>1.989.